(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Immunohistochemistry seems to be important method for differentiation between papillary thyroid carcinoma which is the commonest thyroid cancer and Grave’s disease which may be challenging by light microscopic features only. Objectives:The aim of the study was to evaluate the immunohistochemical expression of CK 19 antibody that is considered a marker of malignancy in papillary thyroid carcinoma and in Grave’s disease and to determine whether CK19 is effective in the discrimination between these two pathological conditions. Methods: In this retrospective study paraffin embedded archival materials from 40 cases including 20 papillary thyroid carcinoma and 10 Grave’s disease in addition to ten normal thyroid tissue were used as a control group, collected from the department of pathology of Al-Yarmook Teaching Hospital for the period between Jan 2009 to Jan 2011. The immunohistochemical expression of CK19 markers was assessed for intensity and extent of staining in semiquantative method. Results:Sixteen of the 20 papillary carcinomas showed diffuse and intense cytoplasmic staining with CK19 (80%), 4 cases showing diffuse faint staining (20%). Seven of the 10 Grave’s cases (70%) are completely negative. The remaining 3 cases showing focal weak staining with CK19 (30%). There was a significant difference in the extent of staining between papillary thyroid carcinoma and Grave’s disease and there was highly significant difference in intensity of staining between them. Conclusions:The staining features of CK19 may be helpful in the differential diagnosis between papillary carcinoma and Grave’s disease with papillary carcinoma like structures. This immunoreactivity should be evaluated with histopathological findings in order to prevent over diagnosis of papillary carcinoma. Keywords: CK19 immunohistochemical expression, papillary thyroid carcinoma, Grave’s disease.